2022
DOI: 10.18632/aging.203889
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a twelve immune infiltration-related lncRNA prognostic signature for bladder cancer

Abstract: The prognosis of bladder cancer patients is strongly related to both the immune-infiltrating cells and the expression of lncRNAs. In this study, we analyzed the infiltration of immune cells in 403 bladder cancer samples obtained from TCGA by applying the ssGSEA to these samples, then dividing them into high/low immune cell infiltration groups. Based on these groupings, we found 404 differentially expressed immune infiltration-related lncRNAs, which were successively analyzed by univariate Cox regression, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…To predict the OS and therapeutic responses in bladder cancer, Wu et al (2020) constructed a TP53-associated immune prognostic signature. Moreover, another study developed a prognostic signature for bladder cancer based on twelve immune infiltration-related lncRNAs ( Liu et al, 2022 ). In our study, we firstly identified a pyroptosis-related prognostic signature for bladder cancer and we could predict the prognosis of each patient by calculating the risk score.…”
Section: Discussionmentioning
confidence: 99%
“…To predict the OS and therapeutic responses in bladder cancer, Wu et al (2020) constructed a TP53-associated immune prognostic signature. Moreover, another study developed a prognostic signature for bladder cancer based on twelve immune infiltration-related lncRNAs ( Liu et al, 2022 ). In our study, we firstly identified a pyroptosis-related prognostic signature for bladder cancer and we could predict the prognosis of each patient by calculating the risk score.…”
Section: Discussionmentioning
confidence: 99%
“…The link between AC008750.1 and NK cells was studied by Sage et al, who revealed that the expression of AC008750.1 was elevated in activated NK cells, and antitumor capabilities of NK cells can be repressed when knocking down the expression of AC008750.1 [ 44 ]. In addition, AL591806.1 and LINC02207 are also potential immune-associated lncRNA signatures in BC and other cancer [ 45 , 46 ]. And LYPLAL1-AS1 has also been verified to engage in the adipogenic differentiation and senescence of human stem cell [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune microenvironment of tumor tissue was evaluated using the estimate R package, and we calculated the evaluation scores of immune and stromal cells. The pan-cancer immune cell infiltration files were downloaded from TIMER 2.0 and used to analyze the distribution of the explored immune cells on different clusters with the help of the limma and pheatmap R packages ( 19 , 20 ). The limma and ggpub R packages were used to perform the differential analysis of the immune microenvironment and immune checkpoints.…”
Section: Methodsmentioning
confidence: 99%